2019
DOI: 10.1186/s12911-019-0831-y
|View full text |Cite
|
Sign up to set email alerts
|

How professional capital and team heterogeneity affect the demands of online team-based medical service

Abstract: Background The provision of medical services by Medical Teams (MT) on Online Healthcare Communities (OHCs) is a novel method employed by geographically-dispersed healthcare professionals to serve one patient simultaneously, allowing patients to receive more specific, targeted and comprehensive advice. As a relatively new method of service delivery, little attention has been paid to identifying the determinants of Team-based Service Demands (TSD). Based on Upper Echelons Theory and Social Exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 68 publications
(79 reference statements)
0
29
0
Order By: Relevance
“…Other researchers, such as Peng and Lee (2005) and Li et al (2019), investigate the specific link between IC, its management and outcomes in health organisations, especially hospitals. Some of these works are based on interviews about the perceptions of physicians and health managers about how IC can support better outcomes.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers, such as Peng and Lee (2005) and Li et al (2019), investigate the specific link between IC, its management and outcomes in health organisations, especially hospitals. Some of these works are based on interviews about the perceptions of physicians and health managers about how IC can support better outcomes.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…This last adjustment is also important for increasing the internal awareness of managers and physicians about the importance and role of IC (Li et al , 2019). Without a clear and visual framework linking IC with what people concretely do, it was quite impossible for managers to consider IC disclosure something useful (Mouritsen and Roslender, 2009).…”
Section: Conclusion Limitations and Further Workmentioning
confidence: 99%
“…Studies on virtual teams have covered different fields, such as open-source software teams, top management teams, and research and development teams in international corporations [4,5]. Only a few studies have explored online MTs [9,17], and confirmed the important role of the leader and members in team output from the transactive memory perspective [17].…”
Section: Medical Teams and Leadership Type In Ohcsmentioning
confidence: 99%
“…Studies have focused on the effects of team leadership, team diversity on virtual team performance [7][8][9]. Some scholars summarized 24 studies on team diversity, concluding that diversity can significantly affect team output/performance in most cases [10].…”
Section: Introductionmentioning
confidence: 99%
“…OHP requires significant engagement from doctors, as they provide doctordriven services [28]. In OHP, doctors provide consultation services, knowledge and information to help patients understand their diseases and obtain treatments [29]. Doctors' contributions, such as providing consultation service and healthcare information, promote the development of such platforms in the long term [30].…”
Section: Commission On Doing a Good Job In Internet Diagnosis And Conmentioning
confidence: 99%